Acupuncture in the Treatment of a Female Patient Suffering from Chronic Schizophrenia and Sleep Disorders - Peggy Bosch; Sabina Lim; Sujung Yeo; Sook-Hyun Lee; Heike Staudte; Maurits van den Noort (Case Reports in Psychiatry)
Background. The use of acupuncture in the treatment of sleep disorders in patients with chronic schizophrenia is investigated. Case Presentation. We report the case of a 44-year-old female outpatient of German origin who had been suffering from long-term schizophrenia and sleep disorders. The patient was treated with manual acupuncture weekly for 12 weeks, and a psychological assessment was performed before, immediately after, and three months after the acupuncture treatment period. In addition, actiwatch data were collected for 14 days both before and after the acupuncture treatment period. Conclusion. Acupuncture treatment led to a decrease in general psychopathology, less severe sleep problems, and markedly improved cognitive functioning (working memory) in the patient; however, the positive and the negative symptoms remained stable. The actiwatch data revealed a beneficial effect of acupuncture, showing better sleep latency, a trend towards better sleep efficiency, and a decrease in the number of minutes that the patient was awake during the night after acupuncture treatment. In sum, this study showed that acupuncture might be beneficial in the treatment of sleep disorders in patients suffering from chronic schizophrenia, but future, large, randomized (placebo), controlled, clinical trials are needed in order to replicate the present preliminary findings.